Interleukin-17 Could Promote Breast Cancer Progression at Several Stages of the Disease - Thomas Welte; Xiang H.-F. Zhang (Hindawi Limited, 2015)
Metastatic disease accounts for more than 90% of deaths from breast cancer. Yet the factors that trigger metastasis, often years after primary tumor removal, are not understood well. Recently the proinflammatory cytokine interleukin- (IL-) 17 family has been associated with poor prognosis in breast cancer. Here we review current literature on the pathogenic mechanisms driven by IL-17 during breast cancer progression and connect these findings to metastasis. These include (1) direct effects of IL-17 on tumor cells promoting tumor cell survival and invasiveness, (2) regulation of tumor angiogenesis, and (3) interaction with myeloid derived suppressor cells (MDSCs) to inhibit antitumor immune response and collaborate at the distant metastatic site. Furthermore, IL-17 might also be a culprit in bone destruction caused by late stage bone metastasis. Interestingly, in addition to these potential prometastasis functions, there is also evidence for an opposite, antitumor role of IL-17 during cancer therapies. We hypothesize that these contradictory roles may be due to chronic, imbalanced versus acute transient nature of the immune reactions, as well as differences in the cells that interact with IL-17+ cells under different circumstances.